Does grazing cause land degradation? Evidence from the sandy Ferlo in Northern Senegal. (30th October 2018) - Rasmussen, Kjeld; Brandt, Martin; Tong, Xiaoye; Hiernaux, Pierre; Diouf, Abdoul Aziz; Assouma, Mohamed Habibou; Tucker, Compton J.; Fensholt, Rasmus
Abstract: It has been widely asserted that a high grazing pressure has led to a reduction in vegetation production at decadal time scales, implying land degradation, in African drylands, and in the Sahel in particular. We test this hypothesis by analyzing spatiotemporal patterns of vegetation production in the northwestern Ferlo in Senegal. Normalized difference vegetation index (NDVI) patterns, here used to represent vegetation production, were determined on the basis of Earth observation MODIS and PROBA‐V data. Furthermore, woody cover was assessed by very high spatial resolution (VHR) imagery. Because livestock is concentrated around deep wells in the dry season for watering, while for management they concentrate daily around pastoral family settlements or camps all year round, we studied the dependence of NDVI on distance from deep wells and camps. Locations of wells and camps were determined by visual inspection of VHR images. We found that 'inverse grazing gradients, ' defined as decreasing NDVI/production with increasing distance, dominated both around wells and camps. Further, we found neither decrease nor increase in woody cover with distance to wells. Both positive and negative trends in wet season NDVI over the period 2000–2016 were identified within the study area, yet temporal trends were predominantly positive in proximity to deep wells. Around pastoral camps, positive NDVI trends were generally elevated relative to the regional average. The results question the validity of claims that high grazing pressure causes land degradation at the landscape scale, yet they show that grazing does lead to substantial spatial redistribution of vegetation production.